2011
DOI: 10.1634/theoncologist.2011-0192
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes and Safety of Single-Agent Sorafenib in the Treatment of Elderly Patients with Advanced Hepatocellular Carcinoma (HCC)

Abstract: Background. With the aging population, hepatocellular carcinoma (HCC) in the elderly represents a significant health burden. We aimed to evaluate and compare the efficacy and tolerability of single-agent sorafenib in treating elderly patients with advanced HCC versus the younger population.Methods. We retrospectively analyzed a consecutive cohort of advanced HCC patients with Child-Pugh A or B liver function and an Eastern Cooperative Oncology Group performance status score of 0 -2 treated with sorafenib. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 48 publications
3
65
0
1
Order By: Relevance
“…It included 172 consecutive patients with advanced HCC and compensated cirrhosis treated with sorafenib and reported that OS (5.32 vs 5.16 months) and AEs related to sorafenib were comparable in a cohort of 35 elderly patients (≥70 years) and one of 135 younger patients (<70 years). Unsurprisingly, the older patients more frequently experienced comorbid cardiovascular conditions, but were also found to suffer grade 3 or 4 malaise, mucositis and neutropenia significantly more frequently than the younger cohort [58].…”
Section: Using Sorafenib In Child-pugh B Patientsmentioning
confidence: 89%
“…It included 172 consecutive patients with advanced HCC and compensated cirrhosis treated with sorafenib and reported that OS (5.32 vs 5.16 months) and AEs related to sorafenib were comparable in a cohort of 35 elderly patients (≥70 years) and one of 135 younger patients (<70 years). Unsurprisingly, the older patients more frequently experienced comorbid cardiovascular conditions, but were also found to suffer grade 3 or 4 malaise, mucositis and neutropenia significantly more frequently than the younger cohort [58].…”
Section: Using Sorafenib In Child-pugh B Patientsmentioning
confidence: 89%
“…In a population of advanced renal cell carcinoma patients aged ≥70 years, sorafenib was shown to be as safe and effective as in patients aged <70 years [23]. More recently, older populations with advanced HCC treated with sorafenib were compared with younger groups [24,25]. A comparison between a group of 35 elderly (age ≥70 years) patients and 137 younger (≤70 years) patients was reported [25].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of sorafenib in elderly patients is supported by a number of studies [69][70][71][72] , which showed similar, or even a trend to longer, overall survival and time to progression in elderly patients compared with younger subjects. Overall, evidence collected to date shows that the efficacy and safety profile of sorafenib is not influenced by age [73,74] .…”
Section: Sorafenibmentioning
confidence: 95%